Acute Intestinal Obstruction in Adults in Kumasi, Ghana - Ohene-Yeboah, M (Ghana Medical Association, 2006)
OBJECTIVES: To describe the causes of acute intestinal obstruction in Kumasi and highlight the associated morbidity and mortality. DESIGN: A proforma based prospective study. SETTING: The study was conducted at the Department of Surgery, Komfo Anokye Teaching Hospital Kumasi, Ghana, from January 1998 to December 2003 inclusive. PARTICIPANTS: All consecutive adult patients admitted to the surgical emergency ward with a clinical diagnosis of acute intestinal obstruction, strangulated hernia, volvulus and intussusceptions were included in the study. Patients diagnosed as incarcerated or irreducible hernia were excluded. RESULTS: Strangulated external hernias 412 (63.2%), and post- operative adhesions 176 (27.2%) accounted for nearly (90.4%) of the 652 cases. All other causes of obstruction including volvolus, neoplasia, strictures and intussusceptions accounted for less than 10% of the patients. Five hundred and eighty - one patients were operated upon and nearly half (242) required bowel resections with an overall mortality of 12 %. Compared with previous reports, adhesive obstructions are increasing whiles strangulated hernias are decreasing. CONCLUSION: Strangulated external hernias and adhesions remain the leading causes of acute intestinal obstruction in our environment. Sustained efforts at elective repair of hernias and research aimed at reducing adhesions are likely ways to reduce the high mortality from acute intestinal obstruction.